2022
DOI: 10.2147/jaa.s383012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Efficacy of Benralizumab in Patients with Blood Eosinophil Count Between 300 and 450 Cells/mm3: A Post Hoc Analysis from the ANANKE Study

Abstract: Benralizumab effectively reduces severe eosinophilic asthma (SEA) exacerbations in patients with a wide range of baseline blood eosinophil count (BEC). Patients included in real-world studies are often characterized by high mean/median BEC, while patients with BEC close to 300 cells/mm 3 are poorly represented. This post hoc analysis from the Italian study ANANKE aims to define the clinical features and corroborate the efficacy of benralizumab in real world in the BEC 300-450 cells/mm 3 subset of patients. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…As previously discussed [ 22 ], the clinical characteristics of the SEA population treated in the ANANKE study (diagnosis of asthma during adulthood, presence of circulating blood eosinophils, moderate airflow obstruction, more than half of the patients suffering from nasal polyposis and other asthma-related comorbidities, frequent exacerbations and a considerable proportion of OCS users) are consistent with the adult-onset, eosinophilic asthma phenotype. As already well-established [ 27 , 28 ] benralizumab is highly effective in this subset of patients regardless of baseline BEC levels [ 25 ] and its effectiveness has been further corroborated in this study with novel long-term data. At 96 weeks, nearly 90% patients were still on treatment.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As previously discussed [ 22 ], the clinical characteristics of the SEA population treated in the ANANKE study (diagnosis of asthma during adulthood, presence of circulating blood eosinophils, moderate airflow obstruction, more than half of the patients suffering from nasal polyposis and other asthma-related comorbidities, frequent exacerbations and a considerable proportion of OCS users) are consistent with the adult-onset, eosinophilic asthma phenotype. As already well-established [ 27 , 28 ] benralizumab is highly effective in this subset of patients regardless of baseline BEC levels [ 25 ] and its effectiveness has been further corroborated in this study with novel long-term data. At 96 weeks, nearly 90% patients were still on treatment.…”
Section: Discussionsupporting
confidence: 79%
“…Patients also experienced an overall improvement in lung function and asthma control, resulting in a decreased utilization of healthcare resources [ 22 ]. Additional post hoc analyses were carried out and revealed that benralizumab maintained its efficacy independently of presence of atopy, body mass index (BMI) [ 22 ], presence of nasal polyps [ 23 ], use of previous biologics [ 24 ] and BEC [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“… 11 Senna et al reported an improvement in asthma control in a patient population with a baseline blood eosinophil count of 300 to 450 cells/μL treated with benralizumab. 33 Additionally, in this study, improvement in ACQ-5 score beyond the minimal clinically important difference was observed in a patient population with a blood eosinophil count of <150 cells/μL (−0.92) and a patient population with a blood eosinophil count of 150 to <300 cells/μL (−1.33). A greater ACQ-5 score improvement was also observed among patients who had eosinophilic asthma characteristics, such as chronic sinusitis, eosinophil count ≥300/µL, higher FeNO (≥37 ppb), and serum total IgE ≥150 IU/mL.…”
Section: Discussionmentioning
confidence: 52%
“…Subsequently, data on 162 severe eosinophilic asthma (SEA) patients were collected over a period of at least 96 weeks with a median exposure to treatment of 98.4 weeks, showing how benralizumab was able to maintain an important reduction of AER over time (94.9%), to eliminate OCS use (60% of patients), while improving lung function (median increase in pre-BD FEV1: +400 ml) and ACT score (median score: 23), with a nearly complete depletion of BEC. 81 Lastly, the post hoc analysis of ANANKE [82][83][84] focused on the best responding asthmatic phenotype to benralizumab, highlighting how a BEC in a range of 300-450 cells/μL and nasal polyposis as comorbidity could be valid indicators of response to treatment, regardless a history of previous biologic therapy. In particular, the efficacy of benralizumab in patients with SEA and nasal polyps confirmed previous data from the ANDHI trial.…”
Section: Mepolizumabmentioning
confidence: 99%